Fine needle aspiration cytology of cervical lymph nodes: Comparison of liquid based cytology (SurePath) and conventional preparation. Issue 1 (25th August 2020) - Budhwar, Archana; Kataria, Sant Prakash; Kumar, Sanjay; Singh, Gajender; Kaushik, Nidhi; Sen, Rajeev
Abstract: Background: Fine needle aspiration cytology (FNAC) is the first diagnostic step in patient with cervical lymphadenopathy because of its simplicity, safety and early availability of the results. Liquid‐based cytology (LBC) is an alternative processing method which is used for both gynecological and nongynecological samples. Literature reviewed show few studies comparing LBC with conventional preparation (CP). Aim: The present study was undertaken to evaluate the efficacy of LBC and comparison of LBC and CP in cervical lymphadenopathy. Materials and Methods: In this prospective study, a total of 75 cases of FNAC with cervical lymphadenopathy were included. The first pass was used for CP followed by LBC with the use of SurePath (SP) technique. Both the smears were compared for cellularity, background containing blood, cell debris, lymphoglandular bodies, stromal fragments, cytoarchitectural pattern, etc., by semiquantitative scoring system. Results: There was no statistical difference in the cellularity, cell architecture, and monolayer cells ( P  > .05). On the basis of background containing blood, cell debris, lympho‐glandular bodies, stromal fragments ( P  < .001), nuclear, and cytoplasmic details ( P  < .05), LBC was found to be superior to CP. Conclusion: LBC is a relatively simple technique and superior to CP in respect of better nuclear and cytoplasmic details with loss of background blood and debris. It has a diagnostic accuracy equivalent to that of CP. However, use of both LBC and CP can result in better diagnostic accuracy.